Physical Education and Sport in Slovakia after the Establishment of Czechoslovakia (1918-1924) - Miroslav Bobrík (Jan Długosz University in Częstochowa, 2019)
Creation of the Czecho-Slovak Republic after the WWI, in 1918, was a milestone also in the development of physical education and sport in Slovakia. New Czecho-Slovak government tried, within the new constitutional conditions, to enforce the Czechoslovak character of the state and to withhold the Hungarian influence in individual towns. Following its multi-national, multi-cultural and multi-confessional history, Slovakia had to get over long-time Hungarian wrongdoing and Hungarization also in the area of sport. Before 1918, the Hungarian and partially also German sport clubs prevailed and any efforts to establish Slovak sport clubs were more platonic than realistic. However, the conditions and circumstances changed and were adapted to the new state layout after 1918.Because of the tense military-political situation at the Czech borders and in Slovakia during 1918-1920, arrival of the Czech and also German sport organizations was postponed until 1921. The Sokol (Falcon) organization started to organize its advertising tours in Slovakia in 1921. Sim-ilarly, the German organizations DTV came to Bratislava in 1921 and to Spiš in 1922. In 1920, the Sokol organization had 93 units with 18 494 members, the RTJ organization had 31 units with 4139 members and the Orol(Eagle) organization had 149 units with 15 772 members. Nationally conscious members of Slovak intelligence were entering the Sokol organization independently of their party membership or political orientation. Bratislava was a typical example of such attitude. The long-time rival of the (originally Czech) Sokol organization was the Orol organization, which formally belonged to the Czecho-Slovak Orol but had also an autonomous management in Slovakia. Physical education in the Orol was only secondary, because the organization was mostly religiously focused. All relevant national physical education, sport, scout or touristic organizations gradually established themselves. Particularly the physical education organizations were ideologically closely connected with political parties. Football, volleyball, basketball, tennis, swimming, wrestling, box and table tennis became the most popular sports during 1918-1924. However, Slovakia lagged behind when talking about the material and technical equipment, swimming pools or gyms. Czech sport enthusiasts, who originally came during 1918-1920 to protect the new republic, often helped with the development and management of the sport clubs as well.